Forward kinematic analysis of Dobot using closed-loop method - Sanjuan De Caro, Javier Dario; Rahman, Mohammad; Rulik, Ivan (Institute of Advanced Engineering and Science, 2020)
Dobot is a hybrid robot that combines features from parallel and serial robots. Because of this characteristic, the robot excels for is reliability, allowing its implementation in diverse applications. Therefore, researchers have studied its kinematics to improve its capabilities. However, to the extent of our knowledge, no analysis has been reported taking into consideration the closed-loop configuration of Dobot. Thus, this article presents the complete analytical solution for the forward kinematics of Dobot, considering each link. The results are expected to be utilized in the development of a dynamical model that contemplates the dynamics of each element of the robot.